Development of the polyglot Asian medicine knowledge graph system - Khoo, Christopher S. G. (2024)
The Polyglot Asian Medicine system hosts a research database of Asian traditional and herbal medicines, represented as a knowledge graph and implemented in a Neo4j graph database system. The current coverage of the database is mainly traditional Chinese medicines with some Malay and Indonesian data, with plans to extend to other Southeast Asian communities. The knowledge graph currently links the medicine names in the original and English languages, to alternate names and scientific names, to plant/animal parts they are made from, to literary and historical sources they were mentioned in, to geographic areas they were associated with, and to external database records. A novel graph visualization interface supports user searching, browsing and visual analysis. This is an example of representing a digital humanities research dataset as a knowledge graph for reference and research purposes. The paper describes how the knowledge graph was derived based on a dataset comprising over 25 Microsoft Excel spreadsheets, and how the spreadsheet data were processed and mapped to the graph database using upload scripts in the Neo4j Cypher graph query language. The advantages of using a knowledge graph system to support user browsing and analysis using a graph visualization interface are illustrated. The paper describes issues encountered, solutions adopted, and lessons learned that can be applied to other digital humanities data.